The Influence of Competence and Technology Adaptation on Employee Performance in the Oil and Gas Industry - Aulia Syafputra; Yuni Pratikno; Bambang Nurakhim (Community Engagement and Emergence Journal (CEEJ), 2026)
The oil and gas industry faces challenges related to digital transformation, operational efficiency, and the improvement of human resource quality. This study aims to analyze the effect of competence and technology adaptation in the oil and gas industry. The research used a quantitative approach with data collection conducted through questionnaires distributed to 60 respondents using the total sampling technique. Data analysis was carried out using multiple linear regression with the assistance of SPSS software. The results showed that competence and technology adaptation have a positive and significant effect on employee performance, both partially and simultaneously. These findings indicate that improving knowledge, skills, and the ability to use technology can enhance employee effectiveness and productivity. This study contributes to the development of human resource management and serves as a reference for companies in improving employee performance through competence development and technology implementation. Future studies are recommended to include other variables such as work motivation and organizational culture.